2014
DOI: 10.1098/rsfs.2013.0064
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative implementation of the endogenous molecular–cellular network hypothesis in hepatocellular carcinoma

Abstract: One contribution of 10 to a Theme Issue 'Computational cell biology: from the past to the future'. A quantitative hypothesis for cancer genesis and progression-the endogenous molecular-cellular network hypothesis, intended to include both genetic and epigenetic causes of cancer-has been proposed recently. Using this hypothesis, here we address the molecular basis for maintaining normal liver and hepatocellular carcinoma (HCC), and the potential strategy to cure or relieve HCC. First, we elaborate the basic ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 58 publications
3
64
0
1
Order By: Relevance
“…When comparing with clinical observation and experimental data, we found that two robust stable states from the model reproduced the main known features of the normal hepatocyte and cancerous hepatocyte at the modular and molecular level (electronic supplementary material, tables S13 and S14, more detailed information in our previous work [31]). As the core endogenous network was constructed using knowledge obtained independently and the stable states of the complex nonlinear dynamical systems were not obvious before analysis, it is striking that a single network can reproduce key features of both normal and cancerous hepatocytes, among other predictions.…”
Section: Normal and Cancerous Hepatocytes Are Robust Stable States Ofmentioning
confidence: 95%
See 1 more Smart Citation
“…When comparing with clinical observation and experimental data, we found that two robust stable states from the model reproduced the main known features of the normal hepatocyte and cancerous hepatocyte at the modular and molecular level (electronic supplementary material, tables S13 and S14, more detailed information in our previous work [31]). As the core endogenous network was constructed using knowledge obtained independently and the stable states of the complex nonlinear dynamical systems were not obvious before analysis, it is striking that a single network can reproduce key features of both normal and cancerous hepatocytes, among other predictions.…”
Section: Normal and Cancerous Hepatocytes Are Robust Stable States Ofmentioning
confidence: 95%
“…In this work, based on the core endogenous molecularcellular network for hepatocytes [18,19,31], we found that the normal hepatocyte and cancerous hepatocyte can be represented by two robust stable states of the core network. Relationship between genetic mutations and biological function can be analysed in this context.…”
Section: Introductionmentioning
confidence: 99%
“…S4 represents stem cell and progenitor cell types, S1 cancer cells (APL), and S12 a normal cell type (neutrophil) 细胞(S4); 有非正常细胞类, 如早熟白血球细胞(S1 今受到越来越多的实验证据支持 [25] . 景观拓扑图还 能直观读出致病和治愈的路径通常不是同一的 [16] ,…”
Section: 事实上 早在20世纪上半叶就已经提出细胞的unclassified
“…The stochastic properties of the network can then be inferred through analysis of a large number of simulation trajectories. However, as the SSA follows high-probability reaction paths, it is therefore inefficient for sampling biologically critical rare events that often occur in stiff multi-scale reaction networks, in which slow and fast reactions are well-separated in time scale [28][29][30][31][32][33]. In addition, assessment of its convergence of simulation trajectories is also difficult.…”
mentioning
confidence: 99%